Asset Pricing and the Foreign Exchange Risk in the Polish Market - Xing, Jingjing (2012)
This study examines the relationship between the cross-section of Polish stock returns and the foreign exchange rates with a sample period from 2002 to 2011. The findings indicate that the foreign exchange risk is priced in the cross-section of Polish stock returns with a sample period spanning 2002 to 2011. Moreover, it is also evident that the relation between the expected returns and the foreign exchange sensitivity is not linear and the foreign exchange sensitivity is larger for stocks with small size and high book-to- market ratios.